Planting of Nectar Plants as Feed of Butterflies Imago in Bantimurung Bulusaraung National Park - Suryanto, Heri; Mangopang , Albert Donatus (Forestry Department, University of Muhammadiyah Makassar, 2023)
Bantimurung Bulusaraung National Park is a forest area designated as a conservation area in Sulawesi. The diversity of flora and the presence of unique wildlife supported by the karst ecosystem are the basis for the protection of thia area. Community presure and habitat destruction is the causes of decreasing butterfly populations. Habitat rehabilitation need to be carried out in order to maintain the butterfly population. The understanding of diversity of butterfly species and the selection of protective tree species and animal nests or food are important aspects for sustainableliyty. Most of the types of forage plants are unknown species, so an understanding of planting methods in the field is needed. The research was conducted in observing the diversity of Rhopalocera (butterfly) species as a preliminary research and planting nectar-producing plants as the main research. Research result showed that Nymphalidae family is highest in species diversity index, Nymphalidae and Papilionidae family are highest in richness index, and all famiies are lowin species dominance index and evenness index. Nimphalidae and Papilionidae family is the largest species has been found. Planting nectar plants i.e mali-mali and dao on degraded land with fertilization treatment showed the best results are 600 grams per planting hole for mali-mali and 900 grams per planting hole for dao.